Multiwall and bamboo-like carbon nanotubes from the Allende chondrite: A probable source of asymmetry. - Hugo I Cruz-Rosas; Francisco Riquelme; Patricia Santiago; Luis Rendón; Thomas Buhse; Fernando Ortega-Gutiérrez; Raúl Borja-Urby; Doroteo Mendoza; Carlos Gaona; Pedro Miramontes; Germinal Cocho (PLoS ONE, 2019)
This study presents multiwall and bamboo-like carbon nanotubes found in samples from the Allende carbonaceous chondrite using high-resolution transmission electron microscopy (HRTEM). A highly disordered lattice observed in this material suggests the presence of chiral domains in it. Our results also show amorphous and poorly-graphitized carbon, nanodiamonds, and onion-like fullerenes. The presence of multiwall and bamboo-like carbon nanotubes have important implications for hypotheses that explain how a probable source of asymmetry in carbonaceous chondrites might have contributed to the enantiomeric excess in soluble organics under extraterrestrial scenarios. This is the first study proving the existence of carbon nanotubes in carbonaceous chondrites.